Descripción botánica de 10 especies de orquídeas del género masdevallia y su importancia económica - Payes Ramírez, Francisco Javier (2011)
In the present work of investigation on the botanical Description of 10 species of orchids of the Masdevalliasort and its economic importance the following objectives were evaluated:1.- To describe to the botany and the agroclimatic location of the 10 species in study.2.- To determine the commercial importance of orchid of I generate Masdevallia. The present work was realized in the Canton Cuenca, Zhucay Sector, Province of the Azuay.The methodology of the work was the following one: the botanical description of the species of this culture was realized for which all the physical aspect of the species in study was exposed, as it is his structure of the foliar and as much floral plant. Also the development of each part was registered that conforms the plant as they are the root, leaves and flowers. In order to be able to describe each one of the species, a brief history of each of them occurred, that is to say, its origin and of where each comes from these species they are the following; Msd.asterotricha, Msd.cardiantha, Msd.carruthersiana, Msd.hirtzii, Msd.mezae, Msd.mendozae, Msd.prodigious, Msd.strobelli, Msd.virgo-cuencae and Msd.wageneriana var. pteroglossa.As far as the culture one occurred to the fundamental principles in the care of these species based on botanical descriptions and the use of the taxonomic, existing keys in specialized Literature. The obtained results indicate that, the adaptation of the 10 species of orchids of Masdevallia demonstrated that exists variability in the results of the different analyzed variables; reason why, a taxonomic study of the same was realized, managing to establish the characteristics of each of them for its final recognition. The Masdevallia sort is distinguished of all the other subtribe by a combination of the six following characteristics: ramicauls shorter than the leaves that take, inflorescences taken laterally of ramicauls with a ring a considerable distance underneath the layer of the abscission; hard petals, especially in half or the margin to labellar; the lip with hinges flexible to the extremity of an extension of the column-foot that is free of the ovary;the axis of the semiround column with a ventral anther, rostellum and a stigma and two pollinia.